MARKETING APPROACH TO FINANCING INNOVATIVE DEVELOPMENT OF THE AGRICULTURAL SECTOR - Sus, T. Y.; Hrechanyk, N. Yu.; Koliedina, K. O. (The actual problems of regional economy development, 2024)
In the innovative development of the agricultural sector of Ukraine, marketing activity is important, which would ensure the effective use of limited financial resources and create conditions for the production of innovations, their promotion and wide use. It is noted that the implementation of the concept of innovative marketing will allow enterprises to quickly find insufficiently satisfied requests for innovations, form an innovative strategy, develop operational plans and manufacture and promote their own innovative products on the market, which will satisfy consumer requests more fully and efficiently. Marketing is aimed at taking into account interests and requests of all participants of the innovation chain and, first of all, the buyer and seller of innovative products. Modern studies of the diffusion of innovations and the mechanism of their spatial distribution are considered. It is noted that in Ukraine, agricultural innovations are associated with the use of mainly domestic scientific developments aimed at intensifying agricultural production, primarily in crop production, with the aim of increasing export volumes and ensuring the economic efficiency of agricultural production, and are evolutionary in nature. Based on the specifics of the agrarian sector, a grouping of innovations was carried out, which allows for the identification of key innovations for each group and the implementation of unified marketing measures, in particular for the study of the promotion of innovations in the agrarian sector. The classification of innovations according to the criterion of financing and marketing approaches has been carried out, which will allow predicting financing for marketing activities and will contribute to the implementation of innovations by business entities. It was noted that the development and implementation of innovations in the agricultural sector is complex due to the influence of industry on agricultural production, the processing industry and the development of innovative infrastructure. Two main approaches to policy formation and innovative economic development models are considered. It was noted that the practice of stimulating the supply of innovations showed significant shortcomings and low efficiency in the use of financial resources as a result of changes in the priorities and volumes of financing of innovative projects in the conditions of reducing expenditures on innovative activities. Marketing activity should be aimed at stimulating the demand for innovations, which will allow more efficient use of financial resources and satisfy the needs of the agricultural sector in innovations of domestic origin. The economic effectiveness of innovative activities in the agricultural sector directly depends on marketing activities to promote innovative products.